Comparative Evaluation of Push-Out Bond Strength at Various Levels for Two Different Size Radicular Posts Cemented with Two Different Resin Cements: An In vitro Study - Neha Vijaykumar; Syeda Amtul Haseeb; Vinaya Kodige Chandrashekar Rao; Kyatsandra Rajagopal Akashata; Mahesh Chikkulikere Swamy; Mahesh Kumar Reddy (Journal of Pharmacy and Bioallied Sciences)
Objective: To evaluate the push-out bond strength at various levels for two different size fiber-reinforced composite resin posts cemented with two resin cements. Materials and Methods: Forty-eight mandibular premolars were divided into four groups based on post size and cement type. Group A used size #01 posts with Allcem core resin cement, Group B used size #01 posts with Maxcem elite resin cement, Group C used size #03 posts with Allcem core resin cement, and Group D used size #03 posts with Maxcem elite resin cement. Samples were sectioned into cervical, middle, and apical levels and subjected to push-out bond strength testing using a universal testing machine. Data were analyzed using ANOVA and t-tests. Results: Group B exhibited the highest mean bond strength (2.84 MPa), followed by Group D (2.68 MPa), Group C (2.57 MPa), and Group A (2.19 MPa). Significant differences were observed among levels and groups. Conclusion: Maxcem elite resin cement provided superior bond strength compared to Allcem core. Larger posts exhibited higher bond strength, although not always statistically significant.